2014
DOI: 10.3389/fpsyg.2014.01318
|View full text |Cite
|
Sign up to set email alerts
|

Individual aptitude in Mandarin lexical tone perception predicts effectiveness of high-variability training

Abstract: Although the high-variability training method can enhance learning of non-native speech categories, this can depend on individuals’ aptitude. The current study asked how general the effects of perceptual aptitude are by testing whether they occur with training materials spoken by native speakers and whether they depend on the nature of the to-be-learned material. Forty-five native Dutch listeners took part in a 5-day training procedure in which they identified bisyllabic Mandarin pseudowords (e.g., asa) pronou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
108
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(126 citation statements)
references
References 57 publications
14
108
4
Order By: Relevance
“…Participants in the single‐talker group did not gain in the compactness of the trained vowels nor did they improve their production accuracy (although their productions were 15% closer to the target after training, which was not significant) . These results are in line with previous perception studies showing that variability is required for the generalization of learning, be it new speakers, new contexts, or new sounds (Lively et al., ; Sadakata & McQueen, , ; Wang et al., ). More importantly, our results demonstrated that the generalization of learning in the multiple‐talker group arises from between‐talker variability in the training materials and not from the acoustic or contextual variability, because contextual variability was matched between the two training conditions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Participants in the single‐talker group did not gain in the compactness of the trained vowels nor did they improve their production accuracy (although their productions were 15% closer to the target after training, which was not significant) . These results are in line with previous perception studies showing that variability is required for the generalization of learning, be it new speakers, new contexts, or new sounds (Lively et al., ; Sadakata & McQueen, , ; Wang et al., ). More importantly, our results demonstrated that the generalization of learning in the multiple‐talker group arises from between‐talker variability in the training materials and not from the acoustic or contextual variability, because contextual variability was matched between the two training conditions.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, in the study by Chang and Bowles, English speakers with no experience learning Mandarin acquired Mandarin tones better in monosyllabic words (characterized by less variation in individual tone contours) than in disyllabic words (characterized by more variation in tone contours). Interestingly, recent studies have shown that novice learners can still benefit from variability if they have strong general perceptual abilities, such as the ability to detect a pitch contour (Antoniou & Wong, ; Perrachione, Lee, Ha, & Wong, ; Sadakata & McQueen, ). The results of these studies suggest that variability interferes with initial learning of L2 contrasts for novice learners with poor perceptual abilities.…”
Section: Background Literaturementioning
confidence: 99%
“…However, low-aptitude perceivers did worse on high-variability as compared to low-variability training. Sadakata & McQueen (2014) showed a similar pattern of results for Dutch learners of Mandarin. An examination of additional language contrasts is needed.…”
Section: Discussionsupporting
confidence: 80%
“…For the monolingual L1 English group, however, this was an unexpected result given the robust improvement observed in Wang et al. (), and the similar facilitatory effects reported in the lexical tone perceptual learning literature (e.g., Barcroft & Sommers, , ; Sadakata & McQueen, ; Shih & Lu, ). The difference between the present study and Wang et al.…”
Section: Discussionsupporting
confidence: 68%